What predicts job satisfaction in Malaysia? - Kamarulzaman, Wirawani; Ibrahim, Mohd Burhan (Elixirjournal.org, 2013)
The purpose of this study is to address the gaps in the literature and to examine the predictors of job satisfaction. In this study, the hypothesized predictors influencing one’s job satisfaction are a) gender, b) age, c) level of education, d) salary, e) role in the job, and f) years of working in the organization. This study used Minnesota Satisfaction Questionnaire (MSQ) as a data gathering tool. The questionnaires were administered to 89 male respondents, and 121 female respondents. For data analysis, Statistical Package for Social Sciences (SPSS) was employed. In addition to conducting a multiple regression analysis (MRA), descriptive statistical analysis was also carried out as part of the data analysis. Of all the predictors studied, results indicated gender as the only significant predictor of one’s job satisfaction. Several recommendations for future studies were also listed.